Política de valorização docente a partir da dimensão 2 do Plano de Ações Articuladas (PAR) 2011-2014: análise do sistema municipal de educação de Rio Verde-GO - Souza, Clésio Feliciano de (2021)
This thesis investigates the Educational Policies for the Valorization of Teachers, within the Municipal Education System, in the municipality of Rio Verde-Goiás in the light of Dimension 2 of the Articulated Actions Plan, from 2011 to 2014. From now on, it highlights the role of how the educational policy of teacher valorization was guided in the PAR of that city. The work is linked to the research line State, Policies and Education Management of the Graduate Program in Education Master's and Doctorate of the Federal University of Uberlândia (UFU). There fore, the general objective is to analyze the educational policies for the Valorization of Teachers and their repercussions on the Municipal Education System of Rio Verde-GO, in light of Dimension 2 of the Articulated Action Plan (PAR) (2011-2014). Regarding the specific objectives, we proposed: a) to investigate the actions defined in dimension 2 of PAR (2011-2014) in the Municipal Education System of Rio Verde - GO and their repercussions on the policy of teacher valorization in that municipality; b) to investigate the process of formulation and implementation of actions concerning the policy of teacher valorization defined in dimension 2 of PAR (2011-2014) in the Municipal Education System of Rio Verde - GO and c) to verify the possible contribution of PAR to the policy of teacher valorization, within the Municipal Education System of Rio Verde-GO, in light of the analysis category training (initial and continued). The research problem can be summarized in the following question: what are the impacts of dimension 2 of PAR (2011-2014) in relation to Teacher Appreciation, in the Municipal Education System of Rio Verde-GO? Whit a methodological procedure, we opted for bibliographic research and documental analysis, as they offer the necessary support to analyze the material produced by the Federal and Municipal governments, especially the PAR (2011-2014). The results allow us to state that, in the case of the PAR (2011-2014) of Rio Verde - GO, we found that the category: initial and continued training are guaranteed by law to teachers, thus, it is up to the leaders, commitment and organization in the search to protect the rights earned by educators. For, in the contemporaneity, there is a considerable concern about these valorization processes, since the PAR, can be understood as a control mechanism of the state, regarding the valorization of teachers, guided by contradiction and regional influences.